Sciellin inhibits senescence and promotes pancreatic cancer progress by activating the notch signaling pathway - Changhao Wu; Dan Luo; Binbin Shi; Shiyu Chen; Chengyi Sun; Zhiwei He; Chao Yu (Scientific Reports)
Abstract Pancreatic cancer (PC) incidence is increasing annually globally, and the five-year survival rate of patients with PC is approximately 10%. Cellular senescence is a regulatory mechanism against cancer that prevents tumor development by inhibiting the proliferation of damaged or abnormal cells. However, the mechanisms underlying cellular senescence in PC is unclear. Sciellin (SCEL) is a precursor protein of the cornified envelope predominantly enriched in epithelial cells. Previous studies have discovered potential links between SCEL and cellular senescence through bioinformatics analysis. Therefore, the specific role of SCEL in cellular senescence and the malignant features of PC are unclear. In vivo and in vitro assays were performed to investigate the role of SCEL in PC cell senescence, proliferation, invasion, and metastasis. Gene set enrichment analysis was used to identify the Notch signaling pathways activated by SCEL, and coimmunoprecipitation was used to detect proteins that interact with SCEL. The results revealed that SCEL was significantly upregulated in PC tissues and cell models and was correlated with poor clinical outcomes. Further investigation revealed that the interaction between SCEL and Jagged-1 promotes the activation of the Notch signaling pathway, effectively inhibiting the senescence of PC cells while enhancing their proliferation, invasion, and metastatic capabilities. Therefore, SCEL is a potential therapeutic target for PC.